A New Interrogation System for FBG Sensors based on Midband Filter with Correction - Ghedira, Sami; Saad, Said (Engineering, Technology & Applied Science Research, 2023)
In this paper, a midband interrogation system for Fiber Bragg Grating (FBG) sensors is presented and its numerical demonstration is reported. The midband interrogation system is based on a finite reflection filter with automatic correction. The filter is used to interrogate the FBG sensors. The strain FBG sensors were used to demonstrate the effectiveness of the proposed systems. The results demonstrate that the proposed system of interrogation has a great resolution (±1 pm) with good stability.